At the Origin of Fantasy: Conversion of Apuleius’ Plot About the Golden Ass in the Remake of C. S. Lewis’ “Till We Have Faces” - Червинская, Ольга Вячеславовна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The article actualizes the paradigm of genre. The history of literature is the evidence rather of a genre metamorphosis of quite a limited number of forms, than of the systematic enrichment with any another experience of genre creation. This is confirmed by the activity of such a form of intertextual exchange between the texts as remakes. This of course applies to the so-called modern fantasy, the origins of which are, at least, in the antique practice and not later, accentuating primarily one of the classic and ancient techniques of creative fantasy formation. It is also about the “outsideness” of the dialogue of cultures in historical time (by M. Bakhtin). Apuleius’ plot of the Golden Ass is polemically interpreted by C. S. Lewis in the novel “Till We Have Faces” in the aspect of pagan and Christian theodicy.